The Role of Location, Product Quality, And Service Quality on Customer Satisfaction in The Culinary Sector - Orlendo, Enosa khalfani; kurniawati, Desi Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The culinary sector plays a significant role in the tourism industry and serves as one of the key drivers of economic growth. In an increasingly competitive business landscape, prioritizing customer satisfaction is crucial for businesses to retain and foster customer loyalty. This research aims to determine the influence of location, product quality, and service quality on customer satisfaction. Method used in this research is quantitative, employing a survey approach with 120 respondents. The research results indicate a t-statistic significance value for Location < 0.05, leading to the conclusion that location has positive and significant effect on customer satisfaction. Subsequently, the t-statistic significance value for Product Quality < 0.05 suggests that product quality also has a positive and significant effect on customer satisfaction. However, the t-statistic significance value for Service Quality > 0.05 indicates that service quality does not have a significant effect on customer satisfaction. Based on the aforementioned, it can be concluded that Hypotheses 1 and 2 of this study are accepted, and Hypothesis 3 is rejected. These findings imply that restaurants need to pay attention to strategic location and good product quality, with the aim of creating customer satisfaction that can strengthen business sustainability in the culinary sector.